Infestation of Head Lice, Pediculus humanus capitis, in Primary School Children at Houn City, Libya (Journal of Academic Research, 2019)
Objective: Pediculosis is a worldwide public health concern, and today, head lice are seen in all socio-economic levels. The infestation usually occurs by head-to-head contact and children, primarily girls, aged 3-12 years are mostly affected. The aim of study was to estimate the incidence and the epidemiological factors related to Pediculus humanus capitis infestation among the primarily schoolchildren population in Houn city. Material and Methods: The present study was performed during March and April 2016 in three primary schools children in Houn, city, Libya, total of 493 schoolchildren (255 Male and 238 Female) was examined for pediculosis humanus capitis. A child was defined as being infested by the presence of live or dead lice (nits, adults and immature). Data was obtained through a questionnaire containing 6 multiple choice questions for the students. Statistical analysis was conducted using the SPSS software package. Categorical variables were defined as the number and percentage (%) and analyzed using the Chi-square test. P values less than 0.05 were accepted to indicate statistical significance.